Quiet ego is associated with positive attitudes toward Muslims - Al-Kire, Rosemary Lyn; Wayment, Heidi A.; Eiler, Brian A.; Callaway, Kutter; Tsang, Jo-Ann (Frontiers in Psychology, 2022)
Well-known predictors of prejudice toward Muslims include social dominance and authoritarianism. However, a gap exists for variables reflecting a rejection or mitigation of ideological motivations associated with prejudice toward Muslims. We examined if quiet ego was related to positive attitudes toward Muslims, and whether this could be explained by lower levels of authoritarianism, social dominance, and the motivation to express prejudice. We explored this possibility across two studies of adults in the U.S. (N = 376; N = 519). In Study 1, regression results showed quiet ego was directly associated with positive attitudes toward Muslims. Study 2 utilized path analyses and found that the direct relationship between quiet ego and positive attitudes toward Muslims was explained by associations between quiet ego and lower endorsement of authoritarianism, social dominance, and the internal motivation to express prejudice toward Muslims. Moreover, these associations held when accounting for several correlates of intergroup attitudes.